2007
DOI: 10.1002/fuce.200700002
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions Between Methanol/Water Molecules and Nafion™ Membrane: An Infrared Spectroscopy Study

Abstract: The intermolecular interactions between methanol/water and Nafion™ membranes have been investigated using IR spectroscopy. The evolution of IR spectra of the Nafion™ membranes, immersed in various concentrations of methanol solution depends strongly on the methanol concentration. The O–H bending vibration modes at 1,636, 1,660 and 1,672 cm–1 associated with the hydrogen bonding of (H3O+…SO3–) as well as (CH3OH2+…SO3–), and at 1,702, 1,717 and 1,711–1,736 cm–1 associated with the hydrogen bonding of (CF2…H–O–CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…1 × 10 −7 cm 2 S −1 . The proton conductivity increased with an increase in water uptake and IEC, which results from the increase in the -SO 3 samples contained a sufficient amount of PSSA to produce a densely tangled IPN structure, effectively preventing MeOH permeability, thereby generating the best selectivity. The membrane without a semi-IPN structure (i.e.…”
Section: Water State and Ion Exchange Capacitymentioning
confidence: 96%
See 2 more Smart Citations
“…1 × 10 −7 cm 2 S −1 . The proton conductivity increased with an increase in water uptake and IEC, which results from the increase in the -SO 3 samples contained a sufficient amount of PSSA to produce a densely tangled IPN structure, effectively preventing MeOH permeability, thereby generating the best selectivity. The membrane without a semi-IPN structure (i.e.…”
Section: Water State and Ion Exchange Capacitymentioning
confidence: 96%
“…We attribute the peak at 1037 cm −1 to a combination of symmetric vibration of the SO 3 H groups [4] and C-H bending of the benzene rings. Unfortunately, asymmetric vibrations representing SO 3 − group asymmetry, expected at ca. 1164 cm −1 were obscured by the intense C-O-C stretching vibration and could not be located precisely.…”
Section: Assignmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…4B was centered at 1638 cm À1 and was attributed to the bending vibration of the eOH group bonded with the ÀSO 3 À group (30,31). The intensity of this band increased after use of the membrane in MFC, which indicated the interactions of beer brewery wastewater molecules with the hydrophilic domains of the cation exchange membrane (31,32). The broad peaks observed were centered at 1538 cm À1 for the membrane used in MFC and were assigned to the bending vibrations of CeH (28) (Fig.…”
Section: Atr-ftir Spectral Analysismentioning
confidence: 99%
“…the solvent viscosity, molar volume, donor properties and the solvent uptake by the membrane. The intermolecular interactions between methanol/water solution mixture and Nafion ® membranes have been investigated using FTIR spectroscopy [6]. Results of FTIR spectra revealed that the methanol molecules show better capability than water molecules to penetrate into the hydrophobic domain of Nafion ® membrane.…”
Section: Introductionmentioning
confidence: 99%